Study of systematics effects on the cross power spectrum of 21 cm line and cosmic microwave background using Murchison Widefield Array data. Issue 2 (3rd December 2018) - Yoshiura, S; Ichiki, K; Pindor, B; Takahashi, K; Tashiro, H; Trott, C M
Abstract: Observation of the 21 cm line signal from neutral hydrogen during the epoch of reionization is challenging due to extremely bright Galactic and extragalactic foregrounds and complicated instrumental calibration. A reasonable approach for mitigating these problems is the cross-correlation with other observables. In this work, we present the first results of the cross power spectrum (CPS) between radio images observed by the Murchison Widefield Array and the cosmic microwave background (CMB), measured by the Planck experiment. We study the systematics due to the ionospheric activity, the dependence of CPS on group of pointings, and frequency. The resulting CPS is consistent with zero because the error is dominated by the foregrounds in the 21 cm observation. Additionally, the variance of the signal indicates the presence of unexpected systematics error at small scales. Furthermore, we reduce the error by one order of magnitude with application of a foreground removal using a polynomial fitting method. Based on the results, we find that the detection of the 21 cm-CMB CPS with the MWA Phase I requires more than 99.95 per cent of the foreground signal removed, 2000 h of deep observation and 50 per cent of the sky fraction coverage.